Determinants of maternal health services utilization in Hlogotlou area at Sekhukhune District of Limpopo Province, South Africa - Baloyi, Mkateko Happiness (My University, 2021)
Background: South Africa’s poor maternal health indicators have resulted from weak maternal health services delivery, including access to quality family planning, skilled birth attendance, emergency obstetric care, and postnatal care for mothers and new-borns. Maternal deaths and disabilities remain a major public health problem in developing countries and maternal mortality is the health indicator which shows the greatest gap between the rich and poor countries. There are global achievements which are substantial reduction in global maternal mortality and an increase in the proportion of childbirths occurring in health facilities. On annual basis there are maternal health outcomes which occurs and these include an estimated 139 million births, an estimated 289 000 women die during pregnancy, childbirth or soon after and lastly an estimate 2.6 million will have stillbirths and 2.9 million infants will die in the first month of life. The purpose of the study was to determine the factors driving maternal health services utilization in rural areas of Limpopo Province. Methodology: The current study was done at Hlogotlou area in Sekhukhune district of Limpopo province and it used a quantitative research approach, that was descriptive cross-sectional study to determine the factors driving maternal health services utilization. The structured questionnaire was used to describe the knowledge levels of pregnant women on utilizing the antenatal services and to describe the utilization of prenatal services by pregnant women. The sampling method was random. The total number of 450 pregnant women participated in the study and all of them were analysed. Data were analysed using STATA version 12 and descriptive statistics were used to describe the data wherein categorical variables, frequencies and percentages were reported. Differences between groups (teenagers, adolescents, adults) were analysed using univariate logistic regression. Results: A total of 450 pregnant women were interviewed majority of women were in the age group 21-25 years, single, unemployed had a secondary educational level. Socio-economic status was assessed using a household wealth index and majority of the pregnant women in the current study were in the medium socio-economic status at 66.4% and majority of the women were using social grants 67.8%. Majority of women get information pertaining to antenatal care from televisions followed by those who v received information from leaflets, radio and those who did not receive information from anywhere at 37.1%, 23.1%, 22.7% and 16.9% respectively. There was a statistical significance difference between those who initiated first antenatal care visit before 12 weeks and after 12 weeks at p-value=0.007. Majority of pregnant women who used televisions as source of information for maternal health care, majority of them were found to be initiating antenatal care after 12 weeks at as compared to those who used radio and leaflets or newspapers as they initiated antenatal care before 12 weeks. Majority of pregnant women in the current study were aware of the antenatal care services rendered at the clinics and they were aware of the fact that antenatal care services rendered at the clinics could assist in detecting the complications related to pregnancies and also reported that these services could reduce the maternal and neonatal morbidity including maternal mortality. There was an understanding of the importance of antenatal care amongst the pregnant women. The predictors of utilization of maternal health services were young age, lower educational level pregnant women who were not married were pregnant women who were in the low socio-economic status. The young pregnant women were 2.2 times more likely to plan their pregnancies and 1.8 times more likely to discuss their pregnancies with their partners or spouses. Pregnant women who were married at a young age were 0.4 times less likely to lack the knowledge about existing for antenatal care at the clinics. Pregnant women with lower educational level were 6.8 times more likely to lack the knowledge about existing for antenatal care at the clinics. Pregnant women who were not married were 2.1 times more likely to go for the first antenatal care booking in the first trimester (1-12 weeks). Pregnant women who were in the low socio-economic status were 1.4 times more likely to lack the knowledge about existing for antenatal care at the clinics and 1.3 times more likely to report that barriers to accessing antenatal care services was either culture, religion or language barrier. Conclusion: The findings of this study highlight the need to address the structural socio-economic drivers of maternal health care utilizations in rural areas of Limpopo Province, South Africa. Timely entry to antenatal care was low in the study area. In order to improve the situation, it is important to provide community-based information, education and vi communication on antenatal care and its right time of commencement. In addition, empowering women and implementing the proclamation designed for the age at marriage should be mandatory up to the local level. Our findings suggested that policies enhancing improved education could benefit health awareness. Key concepts Antenatal care, maternal health care services, pregnant women, utilization.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Antenatal care; Maternal health care services; Pregnant women; Utilization; Prenatal care; Pregnancy; Obstetrics; Maternal health services; Pregnant women